2021
DOI: 10.1111/sum.12771
|View full text |Cite
|
Sign up to set email alerts
|

AI‐enhanced soil management and smart farming

Abstract: Soil and crop management are facing challenges, in particular an increasing pressure to feed a growing population and improve food safety. Smart farming assists in dealing with these issues by incorporating information and communication technologies into farming practice. The Multiponics Vertical Farming (MVF) system is a very promising concept in smart farming that saves space, transportation cost and delivery time. Complicated systems and messy data can be processed by advanced technologies to achieve greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Parameters such as soil, temperature, weight, precipitation, and mugginess are included in this information. In paper [30], the effect of these characteristics on trim development is depicted, and the discoveries are dissected. It has been found that air parameters, soil sort, and soil composition have an effect on edit generation rates.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Parameters such as soil, temperature, weight, precipitation, and mugginess are included in this information. In paper [30], the effect of these characteristics on trim development is depicted, and the discoveries are dissected. It has been found that air parameters, soil sort, and soil composition have an effect on edit generation rates.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…For decision tree models, the tree’s depth is the most significant component because it defines how much the tree may subcategorize data according to the distinctive features of the dataset. However, for the boosted SVR and DTR models, the learning rates and the number of weak estimators are equally important in building efficient models . This work employed the test-set-cross-validation technique as the optimization strategy.…”
Section: Overview Of the Developed Algorithmsmentioning
confidence: 99%
“…Increased encryption and security measures are required due to the increase in data [25]. In order to combine several digital platforms in agriculture, seamless system compatibility is essential [26]. Energy conservation, notably the use of renewable energy for sensors, must be prioritised [27].…”
Section: Challenges: Cost Data Privacy System Compatibility Energy Ma...mentioning
confidence: 99%